Developing core economic parameter sets for asthma studies: a realist review and an analytical framework. Issue 10 (20th October 2020) - Roukas, Chris; Quayyum, Zahidul; Patel, Anita; Fitzsimmons, Deborah; Phillips, Ceri; Hounsome, Natalia
Abstract : Objective: To develop a standardised set of economic parameters (core economic parameter set) for economic evaluations in asthma studies. Design: A systematic literature review and an analytical framework. Outcome measures: Economic parameters used to evaluate costs and cost-effectiveness of healthcare interventions for people with asthma. Data sources: PubMed, the Cochrane Database of Systematic Reviews, the National Health Service Economic Evaluation Database, the Database of Abstracts of Reviews of Effects and the Health Technology Aaaessment Library starting from 1990. Review methods: Research methods were based on the realist review methodology and included a number of non-sequential, iterative and overlapping components, such as developing an analytical framework for the realist review; systematic literature review of economic parameters; identifying and categorising economic parameters; producing preliminary list of core economic parameters. Results: Database searches found 2531 publications of which 224 were included in the systematic review. We identified 65 economic parameters that were categorised into 11 groups to enable the realist synthesis. Parameters related to secondary care, primary care, medication use, emergency care and work productivity comprised 84% of all economic parameters. An analytical framework was used to investigate the rationale behind the choices of economic parameters in these studies. The main framework domains included type of intervention, research population, study design, study setting and a stakeholder's perspective. Conclusion: Past research thus suggests that in asthma study parameters depicting the use of secondary care, primary care, medication, emergency care and work productivity can be considered as core economic parameters, since they apply to different types of studies. Parameters including diagnostics, healthcare delivery, school activity, informal care, medical devices and health utility apply to a particular type of study (or research question), and thus can be recommended as supplemental parameters. PROSPERO registration number: CRD42017067867.